2013
DOI: 10.1177/102490791302000205
|View full text |Cite
|
Sign up to set email alerts
|

Bedside lung ultrasonography for diagnosis of pneumonia

Abstract: Objective The aim of this study was to investigate the accuracy of bedside lung ultrasound (BUS) in the diagnosis of community-acquired pneumonia (CAP) in patients with dyspnoea presenting to the emergency department (ED) and to analyse the characteristic sonographic findings of CAP. Methods After a six-hour training program, BUS procedures were performed between October 2011 and February 2012 to prospectively evaluate patients presenting to the ED with dyspnoea. Chest X-ray (CXR) or computerised tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
0
30
0
3
Order By: Relevance
“…Three studies (30%) used chest CT scan as the gold standard in cases for which LUS and CXR findings were discordant [22,31,35] and four (40%) performed chest CT scan when clinically indicated [21,34,36,37]. Four studies (40%) explained reasons for study withdrawal [22,34,36,37] and only one study (10%) reported non-interpretable results [35]. Nine studies (90%) used a 3.5-5 MHz micro convex transducer [21,22,[31][32][33][34][35][36][37] and one (10%) used a 5-9 MHz convex probe [38].…”
Section: Methodological Heterogeneitymentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies (30%) used chest CT scan as the gold standard in cases for which LUS and CXR findings were discordant [22,31,35] and four (40%) performed chest CT scan when clinically indicated [21,34,36,37]. Four studies (40%) explained reasons for study withdrawal [22,34,36,37] and only one study (10%) reported non-interpretable results [35]. Nine studies (90%) used a 3.5-5 MHz micro convex transducer [21,22,[31][32][33][34][35][36][37] and one (10%) used a 5-9 MHz convex probe [38].…”
Section: Methodological Heterogeneitymentioning
confidence: 99%
“…Four studies (40%) explained reasons for study withdrawal [22,34,36,37] and only one study (10%) reported non-interpretable results [35]. Nine studies (90%) used a 3.5-5 MHz micro convex transducer [21,22,[31][32][33][34][35][36][37] and one (10%) used a 5-9 MHz convex probe [38]. Four studies (33%) provided information regarding time to perform LUS [21,33,36,37] (Table 4).…”
Section: Methodological Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among all 14 studies, 11 were carried out in emergency department (ED) or medical wards (10,(15)(16)(17)(18)(19)(20)(22)(23)(24)(25), and 3 were conducted in intensive care unit (ICU) (14,21,26). Hemithorax was used as the study unit for result interpretation in one study (23), while others counted by patient.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%